PEMANFAATAN MAKANAN OLEH IKAN-IKAN DOMINAN DI PERAIRAN WADUK Ir. H. DJUANDA [Utilization of Food by Dominant Fishes at Ir. H. Djuanda Reservoir] - Nurnaningsih Nurnaningsih; M. F. Rahardjo; Sutrisno Sukimin (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2004)
This study was conducted to reveal the utilization of food resources by fishes that were dominant at Ir. H. Djuanda Reservoir by using food habit and niche breadth analysis. Fish sampling was done from May to October 2003 in four stations of Ir. H. Djuanda Reservoir including its outlet. Stomach content analysis was conducted at laboratorium of Animal Ecology, Center for Biological Sciences IPB, while the plankton analysis was conducted at Research Station of Fish Stock Enhancement in Jatiluhur. It was found that there were four dominant fish species (Astronotus ocellatus, Amphilophus citrinellus t Oreochromis niloticus, Chanos chanos) exsisting in this reservoir. A. ocellatus and A. citrinellus were omnivorous, but C. chanos could be grouped as herbivorous. The plankton species that were found in their stomach were Coelastrum sp., Siaurastrumsp., Pediastrum sp., and Cosmarium sp. O. niloticus had the highest value of niche breadth, while C. chanos had the lowest value of this. It was also found that niche overlap between A. ocellatus and A. citrinellus, was the highest, while that between A. citrinellus and C. chanos was the lowest.